Requirements elicitation and refinement in collaborative research projects. Issue 12 (30th August 2018) - De Angelis, Guglielmo; Ferrari, Alessio; Gnesi, Stefania; Polini, Andrea
Summary: European Union (EU) projects are means of the European Commission for funding research activities. Such projects address challenging research objectives by involving both academic and industrial partners, from several countries. Information and communication technologies–related projects often undertake to deliver a software system prototype. In such a context, most of the typical issues of global requirements engineering may emerge. Partners can have different background and expertise, needs are not sharply defined, and communication is hampered by linguistic and cultural differences. If these issues are not carefully taken into account from the beginning, problems frequently emerge during project execution. This paper presents the experience of applying a customized elicitation and refinement approach in the context of the Learn PAd EU project, which involved about 50 people. The approach combines collaborative elicitation and wiki‐based refinement sessions to come to a set of consolidated requirements. Lessons learnt are discussed as a guidance for researchers dealing with analogous issues in similar contexts. Some of the major observations refer to the importance of initial face‐to‐face meetings when combined with asynchronous remote interactions; the role of moderators that have to encourage collaboration and foster a shared understanding; and the definition of guidelines to select wiki‐based platforms. Abstract : EU Research Projects in ICT often undertake to develop a software prototype. In such a context, most of the typical issues of global requirements engineering may emerge. If these issues are not carefully taken into account, problems frequently emerge during project execution. This paper presents the experience of applying a customized requirement specification approach that combines collaborative elicitation and wiki‐based refinement sessions. Lessons learnt are discussed as guidance for others researchers who will deal with analogous contexts.